2019
DOI: 10.1016/j.molcel.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

RIM and RIM-BP Form Presynaptic Active-Zone-like Condensates via Phase Separation

Abstract: Highlights d RIM and RIM-BP mixture forms liquid-liquid phaseseparation-mediated condensates d Specific multivalent interaction between RIM and RIM-BP is essential for the LLPS d RIM and RIM-BP condensates cluster Ca 2+ channels in solution and on membrane surface d RIM and RIM-BP are plausible organizers of presynaptic active zones

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
226
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 201 publications
(234 citation statements)
references
References 47 publications
(81 reference statements)
7
226
0
1
Order By: Relevance
“…Though many IDPs/IDRs involved in LLPS apply multisite electrostatic and aromatic interactions, dynamic coupled folding‐binding interactions mediated by specific recognition elements can also drive LLPS. For example, interactions between SH3 domain and proline‐rich motif are involved in the LLPS of the nephrin–NCK–N‐WASP system and the RIM–RIM‐BP system . PDZ domain‐mediated binding is required for phase separation of PSD scaffold proteins .…”
Section: Dynamic Contacts and Fuzzy Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though many IDPs/IDRs involved in LLPS apply multisite electrostatic and aromatic interactions, dynamic coupled folding‐binding interactions mediated by specific recognition elements can also drive LLPS. For example, interactions between SH3 domain and proline‐rich motif are involved in the LLPS of the nephrin–NCK–N‐WASP system and the RIM–RIM‐BP system . PDZ domain‐mediated binding is required for phase separation of PSD scaffold proteins .…”
Section: Dynamic Contacts and Fuzzy Interactionsmentioning
confidence: 99%
“…For example, interactions between SH3 domain and proline-rich motif are involved in the LLPS of the nephrin-NCK-N-WASP system and the RIM-RIM-BP system. 189,190 PDZ domain-mediated binding is required for phase separation of PSD scaffold proteins. 191,192 Multivalent arginine-rich linear motifs interact with the NPM1 pentamer, leading to LLPS.…”
Section: Dynamic Contacts and Fuzzy Interactionsmentioning
confidence: 99%
“…Here, we have provided evidence that the GIT1/β-Pix condensates can be recruited to FAs via the GIT1/Paxillin interaction. Numerous observations point to the possibility that FAs, analogous to pre-and post-synaptic signaling assemblies in neurons 9,12 and signaling complexes in immune-synapses 53 , may also be assembled via phase separation. Both cryo-electron tomography and recent super-resolution light microscopy studies have revealed that FAs form specific electron-dense structures.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that formation of membrane-less compartments, also known as biomolecular condensates, via liquid-liquid phase separation is a new mechanism used by cells to concentrate biomolecules, including enzymes, at specific subcellular regions [1][2][3][4] . Membrane-less condensates seem to be widespread in cells and include cellular machineries such as P granule 5 , nucleoli 6 , centrosomes 7,8 , pre-and postsynaptic signaling apparatuses [9][10][11][12] , and stress granules 13,14 . Membrane-less biomolecular condensates display many unique features when compared to traditional stoichiometric assemblies of molecular complexes as well as membrane-enclosed cellular compartments [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation